Artificial intelligence and structural design of inorganic hollow fiber membranes: Materials chemistry - Mubashir, Muhammad; Ahmad, Tausif; Liu, Xiaowei; Rehman, Lubna Muzamil; de Levay, Jean-Pierre Benjamin Boross; Al Nuaimi, Reham; Thankamony, Roshni; Lai, Zhiping (Chemosphere (Oxford), 2023)
A key challenge is to produce the uniform morphology and regular pore design of inorganic hollow fiber membranes (HFMs) due to involvement of multiple parameters including, fabrication process and materials chemistry. Inorganic HFMs required technical innovations via novel structural design and artificial intelligence (AI) to produce the uniform structure and regular pore design. Therefore, this review aims at critical analysis on the most recent and relevant approaches to tackle the issues related to tune the morphology and pore design of inorganic HFMs. Structural design and evaluation of routes towards the dope suspension, spinning, and sintering of inorganic HFMs are critically analysed. AI, driving forces and challenges involved for harnessing of materials are revealed in this review. AI programs used for the prediction of pore design and performance of HFMs have also been explained in this review. Overall, this review will provide the understanding to build the equilibrium in spinning and sintering processes to control the design of micro-channels, and structural properties of inorganic HFMs. This review has great significance to control the new design of membranes via AI programs. This review also explain the inorganic membrane efficiency as algal-bioreactor. [Display omitted] •A key challenge is to produce the regular pore design of inorganic membranes.•Membranes required novel structural design and AI to produce regular pore design.•Fabrication process and materials chemistry controls the structural design of membranes.•Equilibrium in spinning processes controls the structural properties of membrane.•AI could provide new design of membranes via control on spinning parameters.